Red star over the Pacific China's rise and the challenge to U.S. maritime strategy - Yoshihara, Toshi (Naval Institute Press, 2010)
Combining a close knowledge of Asia and an ability to tap Chinese-language sources with naval combat experience and expertise in sea-power theory, the authors assess how the rise of Chinese sea power will affect U.S. maritime strategy in Asia. They argue that China is laying the groundwork for a sustained challenge to American primacy in maritime Asia, and to defend this hypothesis they look back to Alfred Thayer Mahan s sea-power theories, now popular with the Chinese. The book considers how strategic thought about the sea shapes Beijing s deliberations and compares China s geostrategic predicament to that of the Kaiser s Germany a century ago. It examines the Chinese navy s operational concepts, tactics, and capabilities and appraises China s ballistic-missile submarine fleet. The authors conclude that unless Washington adapts, China will present a challenge to America s strategic position.